MIMO OFDM DOA estimation algorithm implementation and validation using SDR platform - Grigoryan, Levon (Array, 2019)
The work is devoted to research in Mobile Station (MS) positioning techniques having opportunity and perspective of using in the next generation communication networks, particularly in cellular networks. Direction of Arrival (DOA) estimation is necessary in many positioning applications and has been well studied by academy and by industry. The main contribution of this work is to design and implement a computationally light direction of arrival estimator on a Multiple Input Multiple Output (MIMO) Software Defined Radio (SDR) platform. Implemented direction of arrival estimator is tested and validated in real conditions and experimental measurements show, that the implemented algorithm can accurately estimate the directions of arrived signals. Used algorithm, estimates direction of arrivals by processing received data of 16-element two dimensional planar antenna array. The algorithm uses initial data received from channel estimators and further process it to obtain direction information. The hardware implementation has been thoroughly analyzed and experimentally validated and open source host code is available on Github.